Efektivitas latihan range of motion (ROM) terhadap gangguan otot pada pasien stroke di lingkungan desa Kotasan Galang - Butar-butar, Maria Haryanti; Saputra, Heri; Bangun, Herianto; Zebua, Arianus; Maryanti, Endang (Journal of Pharmaceutical and Sciences, 2023)
Background: Stroke sufferers suffer from unmovable muscle disorders that are the result of cerebral bleeding. muscle contractions necessary to perform daily activities and a decrease in blood supply to the brain as a result of stroke. Objective: function of the musculoskeletal system with the effectiveness of a range of motion training (ROM) against muscle disorders in stroke patients in the neighborhood of Kotasan Galang village. Methods: The research type is quasi-experimental, using one-group pretest and posttest design approaches. The research intervention was by doing ROM exercises. (Range of motion). The population of stroke patients who experienced muscle disorders of patients using Wilcoxon's trial was 22 patients. Result: Muscle disorders before and after performing the ROM action obtained the minimum muscle disorder value on scale 2 and the maximum muscle disturbance value on scale 4 with an average of 3.20. Conclusion: There is the effectiveness of range of motion (ROM) exercises against muscle disorders in stroke patients in the neighborhood of Kotasan Galang Village.